Rural Special Education Placements: Stability and Change - Douglas W. Halgren; Harvey F. Clarizio (Journal of Research in Rural Education, 1991)
A three year catch-up prospective study of 654 rural special education (SE) students was conducted to determine what proportion had a change in classification and/orprogramming and what factors were associated with change. The study, which represents the first majoreffort to address the issue of stabilityandchange among special education students in rural areas, included all handicapped students from preschool through secondary school. Information was gathered through a record review and parent survey. Change was found to be more common than is generally perceived, as 38.2% of the students had a classification change (21.9% by termination and 16.3% by reclassification). Changes in the type of program occurredfor 32.8% andtime in specialeducation occurredfor 71.2% ofthe students in classroomprograms. Rates of changes varied significantly between classifications. Bivariate analysis revealed that initial grade level and comorbidity were significantly related to classification andprogramming changes. In addition, student10, gender and multidisciplinary (MDT) member consistency were significantly related to programming changes. The student's initial classification was significantlypredictive ofchange in classification andprogramming while 10 and MDT special education teacher membership consistency were significant predictors of change in programming.